Advanced signal processing techniques with EISCAT3D - Stamm, Johann (UiT Norges arktiske universitet, 2022)
A new, modern ionospheric radar, called EISCAT3D, is under construction in northern Fennoscandia. In the first stage, the radar will have three sites, one combined transmit/receiver site shouth of Skibotn, and receiver sites in Kaaresuvanto and Kaiseniemi. The radar will consist of large groups of dipole antennas that are steered by shifting the phase of the transmitted or received signal. The beam steering is performed by a computer such that the radar can form several receive beams simultaneously. The antenna field of EISCAT3D can be divided into groups that can receive separately. This can be used to image how the received signal intensity varies in the area covered by the receiver beam. For EISCAT3D, it will be possible to image the electron density in the E region if the signal is strong enough. Then, imaging can be done with a resolution of around 100 m x 100 m per pixel at a distance of 100 km. Such measurements enable researching the spatial variation for instance in auroral arcs. EISCAT3D will be able to measure the ion velocity with greater presition in time and space than earlier radars. Together with fast antenna steering, this gives new possibilities to estimate electric field and neutral wind in the ionosphere. A newly developed technique shows that EISCAT3D measurements can be used to obtain spatially resolved estimates of electric field and neutral wind in three dimensions. The technique builds upon theory about inverse problems, Maxwell’s equations, and assumptions about continuity and small variations in the neutral wind. With this technique. It will become possible to study how the electric field varies in and around aurora. En toppmoderne ionosfæreradar, kalt EISCAT3D, er under bygging på Nordkalotten. I første omgang får radaren tre lokasjoner, en kombinert sender og mottaker sør for Skibotn og rene mottakere i Kaaresuvanto og Kaiseniemi. Radaren kommer til å bestå av store grupper av dipolantenner som styres ved å forskyve fasen i signalet hver antenne sender ut eller mottar. ...